Sports Injury Prevention: Are we tilting at windmills? - Alderson, J.; Donnel, C. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Injury prevention frameworks (e.g. Translate Research into Injury Prevention Practice) are critical for reducing injury rates. However, their success relies heavily on the available information within each stage of the framework. Using anterior cruciate ligament injury prevention research as a working example; this paper presents a rationale for the cultivation of cross-disciplinary injury prevention research groups and highlights the role of biomechanics in informing each stage of the injury prevention framework.